Acute responses of platelet indices to concentric isotonic and isokinetic contractions in healthy men Abstract - وریا طهماسبی; سجاد احمدی زاد; فریبرز هوانلو; علی اشرف جمشیدی (Shahid Beheshti University)
Purpose: Because acute responses of platelet indices to different muscle contraction modes are importance and different muscle contraction models also have different hormonal and neuromuscular responses present study was designed to investigate the effects of different concentric isotonic and isokinetic contraction and th recovery (Ih-rec) periods on platelet indices. Methods: Ten healthy male subjects (26.9 ±1.7 years) completed two Isotonic and isokinetic contraction test trials with one week interval at an intensity corresponding to 40% of maximal voluntary isometric torque at 70 (MVIT 70) on two legs quadriceps muscle using Biodex Systems Pro 4 which was followed by th recovery. Venous blood samples (5 ml) were obtained before, immediately after exercise and at the end of recovery and were analyzed for platelet count (PLT), Large platelet count rate (PLC-R), mean platelet volume (MPV). platelet wide distribution (PDW) using cell counter Sysmex K-1000 and Lactate concentration using enzymatic methods. Plasma volume changes were estimated from hemoglobin and hematocrit readings before and after each exercise trial. Results: Although both exercise trials without considering type of contraction were followed by a significant increase in corrected PLT. PDW. and MPV (P<0.05). These increases were transient and decreased to pre- exercise level at the end of recovery. PLC-R after exercise and 1h-rec had no significant changes (P>0.05). There was no different between two type of contraction for corrected PLT. PLC-R and MPV (P>0.05) and only PDW and uncorrected PLT increases was different for two type of contraction (P<0.05). Conclusion: In general concentric isotonic exercise is followed by higher levels of PLT and PDW in comparison to concentric isokinetics exercise and results showed that after concentric isokinetic contraction with same training volume in comparison with isotonic contraction rate of some platlet incides increase and thrombocytosis is lower.